Individual and area-level socioeconomic correlates of hypertension prevalence, awareness, treatment, and control in uMgungundlovu, KwaZulu-Natal, South Africa - SLM Madela; NW Harriman; R Sewpaul; AD Mbewu; DR Williams; S Sifunda; T Manyaapelo; A Nyembezi; SP Reddy (BMC, 2023)
Abstract Background Hypertension is the second leading risk factor for death in South Africa, and rates have steadily increased since the end of Apartheid. Research on the determinants of hypertension in South Africa has received considerable attention due to South Africa's rapid urbanization and epidemiological transition. However, scant work has been conducted to investigate how various segments of the Black South African population experience this transition. Identifying the correlates of hypertension in this population is critical to the development of policies and targeted interventions to strengthen equitable public health efforts. Methods This analysis explores the relationship between individual and area-level socioeconomic status and hypertension prevalence, awareness, treatment, and control within a sample of 7,303 Black South Africans in three municipalities of the uMgungundlovu district in KwaZulu-Natal province: the Msunduzi, uMshwathi, and Mkhambathini. Cross-sectional data were collected on participants from February 2017 to February 2018. Individual-level socioeconomic status was measured by employment status and educational attainment. Ward-level area deprivation was operationalized by the most recent (2011 and 2001) South African Multidimensional Poverty Index scores. Covariates included age, sex, BMI, and diabetes diagnosis. Results The prevalence of hypertension in the sample was 44.4% (n = 3,240). Of those, 2,324 were aware of their diagnosis, 1,928 were receiving treatment, and 1,051 had their hypertension controlled. Educational attainment was negatively associated with hypertension prevalence and positively associated with its control. Employment status was negatively associated with hypertension control. Black South Africans living in more deprived wards had higher odds of being hypertensive and lower odds of having their hypertension controlled. Those residing in wards that became more deprived from 2001 to 2011 had higher odds of being aware of their hypertension, yet lower odds of receiving treatment for it. Conclusions Results from this study can assist policymakers and practitioners in identifying groups within the Black South African population that should be prioritized for public health interventions. Black South Africans who have and continue to face barriers to care, including those with low educational attainment or living in deprived wards had worse hypertension outcomes. Potential interventions include community-based programs that deliver medication to households, workplaces, or community centers.